2018
DOI: 10.1161/jaha.118.009149
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Associated With a Strategy of Adjuvant Metolazone or High‐Dose Loop Diuretics in Acute Decompensated Heart Failure: A Propensity Analysis

Abstract: BackgroundIn acute decompensated heart failure, guidelines recommend increasing loop diuretic dose or adding a thiazide diuretic when diuresis is inadequate. We set out to determine the adverse events associated with a diuretic strategy relying on metolazone or high‐dose loop diuretics.Methods and ResultsPatients admitted to 3 hospitals using a common electronic medical record with a heart failure discharge diagnosis who received intravenous loop diuretics were studied in a propensity‐adjusted analysis of all‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
2
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 35 publications
1
52
2
6
Order By: Relevance
“…A meta‐analysis of existing observational data underscores the frequent occurrence of hypokalaemia. In a propensity‐matched analysis of real‐world use of thiazides (combined with lower‐dose loop diuretics) and high‐dose loop diuretics in heart failure patients, thiazides, but not high‐dose loop diuretics, were independent predictors of the occurrence of hyponatraemia and hypokalaemia with an indication towards a higher risk for all‐cause mortality . Given the relative safety of high‐dose loop diuretics in the DOSE‐AHF trial, a preference might be given to initial intensification of the loop diuretic dose before adding a thiazide diuretic .…”
Section: Practical Use Of Diuretics In Acute Heart Failurementioning
confidence: 99%
See 1 more Smart Citation
“…A meta‐analysis of existing observational data underscores the frequent occurrence of hypokalaemia. In a propensity‐matched analysis of real‐world use of thiazides (combined with lower‐dose loop diuretics) and high‐dose loop diuretics in heart failure patients, thiazides, but not high‐dose loop diuretics, were independent predictors of the occurrence of hyponatraemia and hypokalaemia with an indication towards a higher risk for all‐cause mortality . Given the relative safety of high‐dose loop diuretics in the DOSE‐AHF trial, a preference might be given to initial intensification of the loop diuretic dose before adding a thiazide diuretic .…”
Section: Practical Use Of Diuretics In Acute Heart Failurementioning
confidence: 99%
“…In a propensity-matched analysis of real-world use of thiazides (combined with lower-dose loop diuretics) and high-dose loop diuretics in heart failure patients, thiazides, but not high-dose loop diuretics, were independent predictors of the occurrence of hyponatraemia and hypokalaemia with an indication towards a higher risk for all-cause mortality. 103 Given the relative safety of high-dose loop diuretics in the DOSE-AHF trial, a preference might be given to initial intensification of the loop diuretic dose before adding a thiazide diuretic. 42 However, in the CARRESS-HF-trial, the addition of metolazone was an intrinsic part of the stepped pharmacologic algorithm, resulting in the recommendation of thiazides as a second-line agent in the Heart Failure Society of America practical guidelines.…”
Section: Thiazide or Thiazide-like Co-administrationmentioning
confidence: 99%
“…Furthermore, the high risk of WRF in ADHF patients is associated with several pathophysiological processes, including hemodynamic status, activation of the neurohormonal system, the release of in ammatory cytokines and other drug therapies [18][19][20]. Plasma volume reduction leads to WRF in ADHF patients in whom high loop diuretic dose were administered [21].…”
Section: Discussionmentioning
confidence: 99%
“…Diuretics are one of the most valuable and least researched class of agents for heart failure. A recent cohort study suggested that intensification of loop diuretic dose may be a better strategy than using a combination of thiazide and loop diuretics albeit in a patients who probably had low rates of treatment with mineralo-corticoid receptor antagonists (98). Whether furosemide or torasemide is the better diuretic agent is the question posed in the TRANSFORM-HF trial [https://clinicaltrials.gov/ct2/show/NCT03296813].…”
Section: Better Diuretics?mentioning
confidence: 99%